THE IMPLEMENTATION OF DIRECTED READING THINKING ACTIVITY (DRTA) STRATEGY IN TEACHING READING DESCRIPTIVE TEXT USING DISCOVERY LEARNIG - Risa Mulyani; Rissa San Rizqiya (IKIP Siliwangi, 2022)
This study aims to find out the implementation of Directed Reading Thingking Actitivty (DRTA) strategy in reading descriptive text. This research used descriptive qualitative methods. The research used seventh-grade of SMP Pasundan 3 Cimahi. The sample of this research was 20 students. To collect the data researcher used observation. The data was analyzed by categorized, interpreted and concluded. The result showed that the implementation of teaching reading of descriptive text using discovery learning through DRTA strategy was good. It followed the procedure Discovery learning and DRTA strategy. All procedures were applied in the main activity. The students could understand about the text easily and the learning more enthusiastic in learning descriptive text. The students’ felt braver in expressing their opinions, especially in predicting a text in learning reading descriptive text. Keywords: DRTA Strategy, Reading, Descriptive Text